2021
DOI: 10.1002/emp2.12627
|View full text |Cite
|
Sign up to set email alerts
|

Reversible cerebral vasoconstriction syndrome associated with tetrodotoxin poisoning: A case report

Abstract: An 81‐year‐old woman with a history of hypertension and Alzheimer's disease presented to the emergency department because of impaired consciousness. Physical examination revealed acute progressive generalized flaccid paralysis, hypertension, respiratory failure, and pupillary dilation. Although the patient did not complain of headache, head magnetic resonance angiography and magnetic resonance imaging showed multifocal segmental cerebral vasospasm and cerebral infarction in the left occipital lobe. Her family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…As a low dosage of TTX can barely cross the blood–brain barrier [ 20 , 21 ], in a certain dose range, TTX predominantly affects the conduction of the peripheral nervous system and skeletal muscles via the blocking of Na v 1.4, Na v 1.6 and Na v 1.7 [ 19 ]; thus, the influence of TTX on the peripheral nervous system and skeletal muscles requires further investigation. Previous studies showed a trend for self-healing in TTX poisoning [ 22 , 23 , 24 , 25 ], but the process lacked detailed descriptions. Therefore, we established TTX poisoning models via i.m.…”
Section: Discussionmentioning
confidence: 99%
“…As a low dosage of TTX can barely cross the blood–brain barrier [ 20 , 21 ], in a certain dose range, TTX predominantly affects the conduction of the peripheral nervous system and skeletal muscles via the blocking of Na v 1.4, Na v 1.6 and Na v 1.7 [ 19 ]; thus, the influence of TTX on the peripheral nervous system and skeletal muscles requires further investigation. Previous studies showed a trend for self-healing in TTX poisoning [ 22 , 23 , 24 , 25 ], but the process lacked detailed descriptions. Therefore, we established TTX poisoning models via i.m.…”
Section: Discussionmentioning
confidence: 99%